(untitled) (Global Media Journal - German Edition, 2021)
The outbreak of the Coronavirus Disease (COVID-19) has been widely covered on major U.S. media. “Chinese Virus” or “Wuhan Virus” became media buzz words especially at the beginning stage of the outbreak, which was feared to fuel anti-Asian hatred both in the U.S. and worldwide. This study examines the news coverage about COVID-19 in relation to Asians, mainly Chinese and China, on YouTube channels of major U.S. media outlets, and explores the relationship between the media framing and anti-Asian sentiments embedded in the comments beneath the news video. By content analyzing 50 news videos covering COVID-19 and Asians from 5 U.S. media organizations and 5000 comments, the findings suggest that attribution of responsibility and conflict are the most frequently used frames by the news reporting. The results also reveal that suspicion of conspiracy, rather than blaming, emerged as the most frequent theme embedded in hateful comments. One promising finding is that the frequency of hateful comments is significantly lower than that of non-hateful comments across all news frame categories.